Diffusion of molecular hydrogen in carbon aerogel. (March 2016) - Bahn, Emanuel; Czakkel, Orsolya; Nagy, Balázs; László, Krisztina; Villar-Rodil, Silvia; Tascón, Juan M.D.; Demmel, Franz; Telling, Mark T.F.; Fouquet, Peter
Abstract: The diffusion of hydrogen molecules adsorbed in a highly porous carbon aerogel has been studied with quasi-elastic neutron scattering. Hydrogen diffusion in this carbon substrate followed an activated jump process with a single activation barrier. The temperature dependence of the diffusion rate agrees well with previous results from activated carbons and other highly porous carbons. The carbon aerogel sample showed a strongly enhanced conversion between the ortho- and para-hydrogen spin states. The ortho-para conversion process, however, was inhibited for a fraction of the hydrogen molecules. This inhibition process is attributed to a rotational confinement of the hydrogen molecules at the nanometre scale.